Rapid synthesis: Examining the role of coaching in health-system transformations - Waddell, K; Evans, Cara; Sharma, Kartik; Bullock, Heather; Grimshaw, Jeremy M; Lavis, JN (My University, 2020)
An in-depth synthesis of what is known based on the best available global research evidence (i.e., evidence syntheses) and local research evidence (i.e., single studies) as well as experiences from other countries and from Canadian provinces and territories about the role of coaching in health-system transformations in response to a decision-makers’ request. This document was prepared in 90 business days using an ‘all hands on deck’ approach.
Keywords: role; coaching; health-system; transformations